(untitled) (The Journal of Psychology and Sociology, 2017)
The features of the development of views on socio-psychological problems of people with disabilities and the basis of socio-psychological support of disabled people with psychoneurological diseases are discussed in this article. Theoretical analysis of the problem is conducted since the appearance of this phenomenon until today. In the Republic of Kazakhstan there are various organizations in charge of people with psycho-neurological diseases. In these organizations persons with persistent and gross violations of mental health are served. Unfortunately, these facilities are not reaching all those in need of special care. There are difficulties in finding sources of Kazakh scientists on the issue of support of disabled chronic mental patients. At the moment, approaches to the study of the theoretical aspects are of a legislative nature. There is contradiction between the service problem and its theoretical justification. People suffering from psycho-neurological diseases of mild degree are “cut off” from society, because the presence of psychopathology is a contraindication for education and employment. Limitations in communication, in communion with the spiritual and cultural values, attention impairs emotional-behavioral sphere, causes stress and prolonged depression. he empirical data of psychological research are in the article. People with neuropsychiatric diseases (with disability with mental illness) and registered in Department on rendering of special social services of the “Center of social service of the population” of Pavlodar took part in the research. The purpose of this research is study of features of social and psychological support of people with disabilities in the condition of home care services in the Republic of Kazakhstan. Key words: psychological support, disabilities, persons with disabilities, special psychology